PENILAIAN KELAYAKAN FINANSIAL KEBUN KELAPA SAWIT RAKYAT DI KABUPATEN ROKAN HULU - Defidelwina Defidelwina (Agro Ekonomi, 2013)
This study aims to (1) determine the feasibility of people’s business oil plan plantation assessment in terms of financial by using investment criteria, (2) to know the sensivity of people’s business oil palm plantation in price changes of both input output. The research was conducted in Rokan Hulu Regency. The analyzed method used was analysis of the investment criteria of NPV, IRR, BCR, PBP, and BEP. The data used are the primary data obtained though interviews using qesioner. The samples taken by Purposive Sampling from 50 respondents of the people pure self oil palm plantation in Rokan Hulu Regency. The results showed that the people oil palm plantations, either before or after financing is feasible to be implemented. The results of sensitivity analysis of input price increase by 10%, and the FFB selling price is considered fixed and FFB sale price fell by 10% and the price of the production factor fixed, either before r after the financing business is still feasible to be implemented. FFB price changes are more sensitive to changes the value of investment criteria than the production fact price changes.